« Qu’est-ce qu’il y a de pire que cette injustice et cette oppression, oh homme ? » Mouvement féminin, presse et stratégies d’émancipation, Soudan 1950-1956 - Elena Vezzadini (Genre & Histoire)
Starting from 1950, journal articles on the « women question » began to multiply in the main dailies and weekly Sudanese newspapers. They were mostly written by women journalists, but also by some men. The multiplication of women’s voices was unprecedented in modern Sudanese history. In this predominantly Muslim country, at that time the elites practiced a strict gender segregation. To be considered as respectable, women had to be invisible in the public space, her name could not be uttered or even read, and the sound of her voice had not to be heard. The first female journalists, helped by progressive male intellectuals, challenged these norms and worked to make acceptable their visibility, in the newspapers as elsewhere. They worked in a particular context, marked by the elaboration of a nationalist project, the spread of anticolonial ideology, and the political work that would eventually lead to the independence in 1956. The appearance of women’s columns translated the aspirations for a better place for the “Sudanese woman” amidst national debates, and showed the political growth of a new group of women made of educated professionals.